Engulfment of Hb‐activated platelets differentiates monocytes into pro‐inflammatory macrophages in PNH patients. Issue 8 (17th May 2018) - Singhal, Rashi; Chawla, Sheetal; Batra, Harish; Gupta, Sameer; Ojha, Amrita; Rathore, Deepak K.; Seth, Tulika; Guchhait, Prasenjit
Abstract: The distinct response shown by different phenotypes of macrophages and monocytes under various clinical conditions has put the heterogeneity of these cells into focus of investigation for several diseases. Recently, we have described that after engulfing hemoglobin (Hb)‐activated platelets, classical monocytes differentiated into pro‐inflammatory phenotypes, which were abundant in the circulation of paroxysmal nocturnal hemoglobinuria (PNH) and sickle cell disease patients. Our current study shows that upon engulfment of Hb‐activated platelets, monocytes differentiate into M1‐macrophages under M1‐polarization stimulus (GM‐CSF, IFN‐γ + LPS). When grown under M2‐polarization stimulus (M‐CSF, IL‐4 + IL13), the cells exhibited an M1‐like phenotype, secreted elevated levels of pro‐inflammatory cytokines including TNF‐α and IL‐1β, and displayed loss of the secretion of cytokine such as IL‐10 and also phagocytic ability unlike the conventional M2 macrophages. Interestingly, when differentiated under the above polarization stimulus, monocytes from PNH patients expressed high levels of CD80 and phospho‐STAT1, like M1 macrophages. Hemolytic mice also exhibited a gradual increase in monocyte–platelet aggregates in circulation and accumulation of CD80 high macrophages in thioglycollate‐induced inflamed peritoneum. The spleen of the mice was also populated by CD80 high macrophages with compromised phagocytic capacity. Our findings suggest that the hemolytic environment and specifically the Hb‐activated platelets, which are abundant in circulation during intravascular hemolysis, closely regulate monocyte differentiation. Abstract : After engulfing Hb‐activated platelets, monocytes from healthy individuals differentiate into pro‐inflammatory M1 or M1‐like macrophages in presence of M1‐ or M2‐polarization stimulus. Besides, the monocytes from PNH patients, positive for both intracellular Hb and platelets, differentiate into M1 macrophages in presence of either of the above stimuli in vitro.